HALAL CERTIFICATION EDUCATION AND GUIDANCE FOR SEMAR MESEM CHICKEN SLAUGHTERHOUSE (RPA) MICRO BUSINESS IN BANJARSENGON VILLAGE, PATRANG SUB-DISTRICT, JEMBER REGENCY - Hertamawati, Rosa Tri; Prasetyo, Anang Febri; Imam, Shokhirul; Rahmasari, Reikha; Prayitno, Agus Hadi; Suryaningsih, Wahyu (Universitas Airlangga, 2025)
Products from slaughtered animals need to have halal certification to ensure the peace of mind of Indonesian consumers, most of whom are Muslims. The development of micro-scale poultry slaughtering businesses has raised questions about whether chicken meat circulating in the community meets the requirements of safe, healthy, intact and halal (ASUH) quality. The purpose of this activity is to provide education, socialization, and assistance in obtaining halal certification to expand marketing and increase the turnover of entrepreneurs at the Semar Mesem Chicken Slaughterhouse (RPA). The method used is to conduct socialization through FGD and assistance in submitting halal certification in the field. Socialization and technical guidance regarding halal and halal certification were carried out by inviting speakers from the Madani Halal Center. The FGD activity was attended by business owners and employees with a total of 25 participants. The activity was assistance in preparing administrative files for submitting halal certification, determining the halal management team, preparing the Halal Assurance System (SJH) manual, facilitation assistance and education on halal policies, and assistance in online registration for halal certification through SiHalal. Participants’ knowledge after the socialization increased from 16% to 80%. After going through these stages, it is hoped that RPA Semar Mesem can immediately obtain a halal certificate for its business.